Efeito do tipo de cobertura em silos de superfície sobre o perfil fermentativo, composição químico-bromatológica e estabilidade aeróbia de silagens de milho ao longo da descarga - Cesar Neto, José Maria (2020)
The qualitative factors related to the impermeability offered by plastic films for the coating of horizontal silos have great relevance when it comes to conducting an adequate fermentation process, preventing gas exchange and consequent inhibition of opportunistic aerobic microorganisms, leading to greater conservation of value nutritional value of the ensiled material. The objective of this work was to evaluate the effectiveness of the type of cover in surface silos on the fermentative profile, chemical-bromatological composition and aerobic stability of corn silages, distinguishing them by the specificities in their coatings, silage collection locations in the panel of the silos, and collection times at the respective locations. The trial period comprised 30 days. Where an experimental design was used in a scheme of sub-sub-divided plots, and as for the nature of the factors used, similarly to the factorials it took place quantitatively according to the type of coverage, place of collection in the silos and time of collection. The experiment had 2 plots [silo 1 (double-sided polyethylene plastic film - white and black (200 µm thick), and silo 2 (internally wrapped with polyamide plastic film (45 µm thick), coated with plastic film of double-sided polyethylene - white and black (200 µm thick) on the oxygen barrier film)], each plot held 3 sub-plots (Top, middle and bottom), and each sub-plot held 3 sub-plots ( 0, 12 and 24 hours after the opening of the silos), where the repetitions occurred during the collection days (R1 = day 0; R2 = day 7; R3 = day 15; R4 = day 21 and R5 = day 30), totaling 18 factorial combinations and five repetitions per treatment. It was possible to verify a great influence of the types of cover on the nutritional conservation of the corn silages, being observed effect for the majority of the evaluated variables regarding the bromatological composition in relation to the type of silo coating (except crude protein (PB) and lignin (LIG )), position (dry matter (DM), mineral matter (MM), PB, ether extract (EE), hemicellulose (HEM), non-fibrous carbohydrates (CNF) and silo versus position interaction (MS , MM, PB, EE, CNF) As for the fermentative profile, it can be seen as well as for silo 2 in its evaluation of the bromatological composition, the best results regarding the fermentative pattern, where a significant effect was found (P <0.05) regarding the levels of organic acids (lactic acid (AL), acetic acid (AA) and propionic acid (AP) (except butyric acid (AB)) produced in both silos. The double layer coated silo (silo 2) exhibited a greater capacity for preserving the nutritional value of forage due to its high impermeability to oxygen, reducing gas exchange with the medium as much as possible, thus contributing to disadvantage the conditions of the medium to the development of opportunistic microorganisms, resulting in a better fermentative profile.